Penguatan Partisipasi Didalam Akuntabilitas Pembangunan Desa - Agus Prianto (Universitas Merdeka Malang, 2018)
Autonomous systems change and change (amendment) as the goal of accelerating development amidst social change. Based on Law 23 of 2014, the authority of the Village Government to design development in accordance with the needs of the community that requires the existence of public participation. Principles of Participation in Development make the system of Democracy a moral development and as a mechanism of social system of development in the village. The high participation of Masyasrakat can create accountability in the function of the Village Command by institutionalizing the community able to play an active role in the planning and supervision of village development.DOI: https://doi.org/10.26905/pjiap.v3i1.2268